2022
DOI: 10.1002/hpja.563
|View full text |Cite
|
Sign up to set email alerts
|

Communication of nutrition information by influencers on social media: A scoping review

Abstract: Issue addressed: Although government promoted public health, social media and media campaigns have communicated nutrition information, the Australian population remains chronic under-consumers of fruit and vegetables and overconsumers of ultra-processed foods. This scoping review aimed to determine how social media influencers (SMI) communicate nutrition information and the factors that influence the popularity of messages. Identified factors could inform how governments may utilise social media to impact posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 40 publications
(172 reference statements)
1
26
0
2
Order By: Relevance
“…Health professionals in the online health space may need to take alternative approaches. For example, engagement with groups who are most likely to publicly share on their networks (Lifestyle Mavens) and using existing influencers to connect with at risk groups [ 47 ]. Indeed, social media may not be the communication method of choice for connecting and influencing those Blissfully Unconcerned at all and connecting to such individuals may require very different approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals in the online health space may need to take alternative approaches. For example, engagement with groups who are most likely to publicly share on their networks (Lifestyle Mavens) and using existing influencers to connect with at risk groups [ 47 ]. Indeed, social media may not be the communication method of choice for connecting and influencing those Blissfully Unconcerned at all and connecting to such individuals may require very different approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Australian researchers have observed that young adults, particularly females, perceive empathetic language as significantly more persuasive compared to authoritative messages [56]. In a review of social media influencers' communications, Rogers et al identified the use of positive, humorous, motivational, inspirational, accusatory and heroic tones of nutrition messages as well as language techniques such as exaggeration and rhetorical questions [66].…”
Section: Language and Tonementioning
confidence: 99%
“…In societies dominated by the economy and the media, individuals are subject to influences from a wide range of information sources (TV, internet, film documentaries, social media), such as advertising of foods and supplements, the opinions of researchers and experts in nutrition, health or fitness, and have improved access to scientific studies ( 66 , 67 ). In recent years, different forms of diet frequently were the subject of a – sometimes highly emotional – debate in public and digital media.…”
Section: Hypotheses On Classical Placebo and Nocebo Effects In Diet C...mentioning
confidence: 99%